The effect of SFL-based genre instruction on Iranian EFL learners' performance in story reproduction - Farshid Sarmadi Kia; Nader Assadi Aydinloo; Masood Zoghi (Universitas Islam Malang, 2022)
This study aimed at investigating the effect of SFL-based genre instruction on Iranian EFL learners' performance in story reproduction. For this purpose, the researcher selected 38 EFL learners through administration of Oxford Placement Test (OPT) and assigned them into experimental and control groups and both groups took an oral reproduction pre-test. Then, in the control group, only common class procedures such as pair work, small-group discussion, and whole class discussion were applied whereas in the experimental group, SFL-based genre analysis of the short stories was conducted by the teacher. At the end of the study, both groups took the post-test. The results of the study revealed a higher amount of increase in the fluency and accuracy scores of the participants in the experimental group in comparison to the control group. The findings of the present study can be advantageous for teachers, syllabus designers, curriculum developers, and Ministry of Education in developing genre-based course for language learners.